AMS Radiocarbon Dates on Peat Section Related with Tephra and Archaeological Sites in Carlisle Island, the Islands of Four Mountains, Alaska. Issue 6 (28th December 2017) - Okuno, Mitsuru; Izbekov, Pavel; Nicolaysen, Kirsten P; Sato, Eiichi; Nakamura, Toshio; Savinetsky, Arkady B; Vasyukov, Dmitrii; Krylovich, Olga A; Khasanov, Bulat; Miranda, Jonathan; Persico, Lyman; Hatfield, Virginia; et al.
ABSTRACT: We obtained radiocarbon ( 14 C) dates with accelerator mass spectrometry (AMS) of vascular plant samples and a charcoal sample collected from peat deposits near the prehistoric village site informally designated CR-03 on Carlisle Island in the Islands of Four Mountains group, Alaska, to determine the eruption age of the CR-02 tephra. A fine vitric ash erupted from Okmok caldera, Umnak Island (ca. 2 ka BP) was also discovered in the bog. The ages of the CR-02 tephra and Okmok II ash are estimated to be 1050 and 2000 cal BP, respectively. Because both tephras are distinctive and widespread, these are important chronostratigraphic markers for archaeological sites in this island group. The 14 C dates obtained from this bog are 800 years younger than the dates of the charcoal fragments from cultural layers in the Unit 3 of prehistoric village site CR-02 (AMK-0003).